Influence of single nucleotide polymorphisms on thrombin generation in factor V Leiden heterozygotes - Segers, Olivier; Simioni, Paolo; Tormene, Daniela; Castoldi, Elisabetta (Thrombosis and Haemostasis, 2014)
Carriership of the factor V (FV) Leiden mutation increases the risk of venous thromboembolism (VTE) ~4-fold, but the individual risk of each FV Leiden carrier depends on several co-inherited risk and protective factors. Under the hypothesis that thrombin generation might serve as an intermediate phenotype to identify genetic modulators of VTE risk, we enrolled 188 FV Leiden heterozygotes (11 with VTE) and determined the following parameters: thrombin generation in the absence and presence of activated protein C (APC); plasma levels of prothrombin, factor X, antithrombin, protein S and tissue factor pathway inhibitor; and the genotypes of 24 SNPs located in the genes encoding these coagulation factors and inhibitors. Multiple regression analysis was subsequently applied to identify the (genetic) determinants of thrombin generation. The endogenous thrombin potential (ETP) showed a striking inter-individual variability among different FV Leiden carriers and, especially when measured in the presence of APC, correlated with VTE risk. Several SNPs in the F2 (rs1799963, rs3136516), F10 (rs693335), SERPINC1 (rs2227589), PROS1 (Heerlen polymorphism) and TFPI (rs5940) genes significantly affected the ETPAPC and/or the ETP+APC in FV Leiden carriers. Most of these SNPs have shown an association with VTE risk in conventional epidemiological studies, suggesting that the genetic dissection of thrombin generation leads to the detection of clinically relevant SNPs. In conclusion, we have identified several SNPs that modulate thrombin generation in FV Leiden heterozygotes. These SNPs may help explain the large variability in VTE risk observed among different FV Leiden carriers.
Keywords: Factor V Leiden; intermediate phenotype; single nucleotide polymorphism; thrombin generation; venous thromboembolism